The Role of Tissue Doppler Imaging in Predicting Left Ventricular Filling Pressures in Patients Undergoing Cardiac Surgery: An Intraoperative Study. Issue 3 (27th November 2012) - Kumar, Kanwal; Nepomuceno, Roman G.; Chelvanathan, Anjala; Golian, Mehrdad; Bohonis, Sheena; Cleverley, Kelby; Ravandi, Amir; Mackenzie, Scott; Jassal, Davinder S.
<x xml:space="preserve">Abstract</x> Introduction: The perioperative management of patients undergoing cardiac surgery usually requires the accurate assessment of left ventricular filling pressures (LVFP). The gold standard for determining LVFP involves the use of pulmonary artery catheters (PAC). Using tissue Doppler indices (TDI) obtained by transthoracic echocardiography, the ratio of early transmitral filling velocity to the corresponding early mitral annular velocity (E/E′) has a strong correlation with pulmonary capillary wedge pressure (PCWP). Little is known, however, on whether this relationship between E/E′ and PCWP is valid intraoperatively using transesophageal echocardiography (TEE) during cardiac surgery. Objective: The objective of our study was to determine whether TDI obtained by intraoperative TEE during cardiac surgery can accurately estimate PCWP using PAC as the gold standard. Methods and Results: A total of 34 patients (26 males, mean age 64 ± 9 years) undergoing cardiac surgery were prospectively enrolled between 2010 and 2011 at a single tertiary care center. Conventional diastolic and tissue Doppler parameters were evaluated using intraoperative TEE with concurrent PAC monitoring before and after cardiopulmonary bypass (CPB) surgery. At both pre‐ and post‐CPB, there was no significant correlation between lateral, septal, and mean E/E′ obtained by TEE and PCWP. Conclusion: Intraoperative TEE was unable to accurately predict LVFP in patients undergoing cardiac surgery. PAC may continue to be the gold standard in the assessment of LVFP for this patient population.